Palladium-Catalyzed Reduction of Acid Chlorides to Aldehydes with Hydrosilanes - Fujihara, Tetsuaki; Cong, Cong; Iwai, Tomohiro; Terao, Jun; Tsuji, Yasushi (Synlett, 2012)
An efficient synthesis of aldehydes from acid chlorides with hydrosilanes as a reducing agent in the presence of a palladium catalyst has been achieved. A simple mixture of commercially available Pd(dba)2 and Mes3P as a catalyst realized the reduction of various acid chlorides including aliphatic acid chlorides and α,β-unsaturated acid chlorides to the corresponding aldehydes in good to high yields under mild reaction conditions.
Keywords: acid chloride; aldehyde; hydrosilane; palladium; phosphine